Two spin-canting textures in the antiferromagnetic phase AF1 of MnWO4 based on the new polar atomistic model in P2. (2nd March 2018) - Park, S-H; Liu, B-Q; Behal, D; Pedersen, B; Schneidewind, A
Abstract: The low temperature antiferromagnetic (AF) phase of MnWO4 (the so-called AF1 phase) exhibits different spin-canting configurations at two Mn 2+ sublattices of the (3 + 1)-dimensional magnetic structure. The suggested superspace group P 2.1 ′ ( α, 1 / 2, γ ) 0 s is a significant consequence of the polar space group P 2 true for the nuclear structure of MnWO4 . Density functional theory calculations showed that its ground state prefers this two spin-canting system. The structural difference between two independent atomic sites for Mn (Mn a, Mn b ) is too small to allow microscopically detectable electric polarisation. However, this hidden intrinsic polar character allows AF1 two commensurately modulated spin-canting textures. This is considered as the prerequisite onset of the improper ferroelectricity enhanced by the helical spin order in the multiferroic phase AF2 of MnWO4 .